[18F]-Fluorodeoxyglucose Uptake as a Marker of Residual Anaplastic and Poorly Differentiated Thyroid Carcinoma Following BRAF-Targeted Therapy - Dagher, Samir A.; Learned, Kim O.; Dagher, Richard; Wang, Jennifer Rui; Zhao, Xiao; Hosseini, S. Mohsen; Maniakas, Anastasios; Cabanillas, Maria E.; Busaidy, Naifa L.; Dadu, Ramona; Iyer, Priyanka; Zafereo, Mark E.; et al. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Neoadjuvant BRAF-directed therapy and immunotherapy followed by surgery improves survival in patients with BRAFV600E-mutant anaplastic thyroid carcinoma (ATC), more so in those who have complete ATC pathologic response. This study assesses the ability of FDG-PET to non-invasively detect residual high-risk pathologies including ATC and poorly differentiated thyroid carcinoma (PDTC) in the preoperative setting.MATERIALS AND METHODS: This retrospective, single-center study included consecutive BRAFV600E-mutant ATC patients treated with at least 30 days of neoadjuvant BRAF-directed therapy and who underwent FDG-PET/CT within 30 days prior to surgery. The highest pathologic grade observed for every head and neck lesion resected was recorded. Each lesion on pre-operative PET/CT was retrospectively characterized. The primary endpoint was to contrast the standardized uptake normalized by lean body mass (SULmax) for lesions with residual high-risk (ATC, PDTC) versus low-risk pathologies (papillary thyroid carcinoma, negative). An optimal SULmax threshold was then identified using a ROC analysis, and the ability of this threshold to non-invasively and preoperatively risk-stratify patients by overall survival was then evaluated with a Kaplan-Meier plot.RESULTS: 30 patients (mean age 66.5±9.0; 17 males) were included in this study, with 94 surgically sampled lesions. Of these lesions, 57 (60.6%) were low-risk (39 negative, 18 papillary thyroid carcinoma) and 37 (39.4%) were high-risk (29 ATC, 8 PDTC). FDG uptake was higher for high-risk compared to low-risk pathologies: median SULmax 5.01 [IQR 2.81 – 10.95] versus 1.29 [IQR 1.06 – 3.1] (P<.001, Mann-Whitney U test). The sensitivity, specificity, and accuracy for detecting high-risk pathologies at the optimal threshold of SULmax ≥ 2.75 were 0.784 [95% CI 0.628–0.886], 0.702 [95% CI 0.573–0.805], and 0.734 [95% CI 0.637–0.813], respectively. Patients with at least 1 high-risk lesion identified with the aforementioned cut-off had a worse prognosis compared to patients without high-risk lesions in the head and neck: median OS for the former group was 259 days and was not attained for the latter (P=.038, log-rank test).CONCLUSIONS: Preoperative FDG-PET non-invasively identifies lesions with residual high-risk pathologies following neoadjuvant BRAF-directed targeted therapy and immunotherapy for BRAF-mutated ATC. FDG-PET avidity may serve as an early prognostic marker which correlates with residual high-risk pathology in BRAF-mutated ATC following neoadjuvant therapy.ABBREVIATIONS: ATC = anaplastic thyroid carcinoma; IQR = interquartile range; OS = overall survival; PDTC = poorly differentiated thyroid carcinoma; PTC = papillary thyroid carcinoma; ROC = receiver operating characteristic; SUL= standardized uptake value normalized by lean body mass.